2004
DOI: 10.1002/eat.10213
|View full text |Cite
|
Sign up to set email alerts
|

Axis I comorbidity onset and parasuicide in women with eating disorders

Abstract: The eating disorder may be secondary to a mood disturbance in women with parasuicidal histories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 16 publications
1
26
1
1
Order By: Relevance
“…In addition, most of the study participants identified themselves as White. Furthermore, we did not identify community or clinical adults with eating and noneating related problems to evaluate stronger evidence for the generalizability of scores to other nonclinical and clinical samples (see e.g., Oliosi & Grave, 2003;Wildman et al, 2004). Future studies should thus evaluate the extent to which the present findings generalize to nonclinical and clinical samples across cultural groups and different regions in the United States.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, most of the study participants identified themselves as White. Furthermore, we did not identify community or clinical adults with eating and noneating related problems to evaluate stronger evidence for the generalizability of scores to other nonclinical and clinical samples (see e.g., Oliosi & Grave, 2003;Wildman et al, 2004). Future studies should thus evaluate the extent to which the present findings generalize to nonclinical and clinical samples across cultural groups and different regions in the United States.…”
Section: Discussionmentioning
confidence: 82%
“…We conducted comprehensive reviews of the relevant self-report instruments and previously published investigations (see e.g., DSM-IV-TR, APA, 2000; Anderson et al, 2002;Cull & Gill, 1982;Favaro & Santonastaso, 1999;Garner, 1991;Oliosi & Grave, 2003;Orbach & Mikulincer, 1998;Sansone & Sansone, 2002;Wildman, Lilenfeld, & Marcus, 2004). In addition, we conducted semistructured individual interviews with psychiatric inpatients and nonclinical adolescents and adults regarding personal feelings, attitudes, and behavioral practices toward a number of bodily experiences.…”
Section: Phase 1: Item Generationmentioning
confidence: 99%
“…In some instances, depressive symptoms are evident prior to the onset of the ED or SUD (primary mood disorder). Wildman, Lilenfeld and Marcus (2004) found that major depression preceded the onset of an ED in 33 % of their female participants. Abraham and Fava (1999) reported that AUD followed the first depressive episode by 4.7 years and cocaine use occurred 6.8 years after the onset of depression.…”
Section: To Manage Mood Disordersmentioning
confidence: 97%
“…19 Psychiatric diagnostics revealed that the BNG had significantly more patients with borderline personality disorder than the MDG (cf. Bulik et al, 3 Verkes et al, 36 Wildman et al, 37 Yen et al 38 ).…”
Section: Resultsmentioning
confidence: 94%